Cs, O coadsorption on Al0.5Ga0.5N(0001) surface. (February 2022) - Ji, Yanjun; Bian, Li; Liu, Ni; Wang, Junping; Wang, Caifeng; Du, Yujie; Liu, Youwen
Abstract: First-principles density functional theory (DFT) simulations have been performed to investigate the adsorption of Cs and O atoms on the surface of (2 × 2) Al0.5 Ga0.5 N(0001). The adsorption energy, dipole moment, and bond population of atoms of the surface of (2 × 2) Al0.5 Ga0.5 N(0001) are analyzed. It is found that the adsorption energy of Cs, O coadsorption is less than that of Cs adsorption only for all the surfaces, Cs, O coadsorption leads to stability and improves the surface structure comparing with the adsorption of Cs only, especially when Cs coverage is 0.75 ML. At this coverage, we found that the H3 is the most ideal adsorption site where 2Cs + O + Cs form the adsorption structure, responsible for ionic bonds between Cs–O and Cs–Cs. In the case of O adsorption, the absorption edge energy and intrinsic absorption peak value increase which consequently enhance the quantum efficiency. On the other hand, at 1 ML Cs coverage, it is inferred that only T1 site is stable and the dipoles are less than that of 0.75 ML Cs coverage. Moreover, the dipoles of Cs surface at T1 and BN sites are negative which prevents escaping of electrons, while plastic deformation is found in the BN and H3 surfaces. Highlights: The adsorption of Cs on Al0.5 Ga0.5 N(0001) surface has been investigated, over-cesiated occurs at coverage 0.75 ML. The ideal model of Cs, O coadatoms on Al0.5 Ga0.5 (0001) surface is 2Cs + O + Cs at H3 site for 0.75 ML coverage. The adsorption of O improves the absorption peak and increases photocurrent for photocathode.